Understanding visitor-resident relations in overtourism: developing resilience for sustainable tourism - Cheung, Ka Shing; Li, Ling-Hin (Journal of sustainable tourism, 2019)
While almost all travel destinations seek to increase tourists, less attention is paid to balancing the growth in tourists against consequent visitor-resident irritants, which is essential if the objective is to make tourism more sustainable. Overlooking the carrying capacity of a destination is a common mistake committed when formulating travel visa policies. Overtourism is a term recently used to contextualize this potential hazard to many popular tourist destinations worldwide. One notable case in point is the "multiple-entry permit" policy implemented in Hong Kong which is causing conflicts between mainland Chinese visitors and Hong Kong residents. To investigate the overtourism phenomenon in Hong Kong we develop a hysteresis model. We hypothesized that ceteris paribus, the implementation of a "multiple-entry permit" policy would lead to an overwhelming growth in day-trippers and cause a permanently negative cointegrating relationship with residents' sentiment. We confirmed our hypothesis by using the bound tests of Autoregressive-Distributed Lag models. Our findings suggest that policymakers should note that the deterioration in visitor-resident relations from overtourism may exhibit a significant hysteresis effect that will persist far beyond the original stimulus. "Developing resilience in tourism" and "exploring sustainable degrowth" are discussed as potential strategies for long-term tourism growth.